Stability of semi-Markov risk processes in schemes of averaging and diffusion approximation - Goncharova, S. Ya.; Svishchuk, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the asymptotic stability of semi-Markov risk processes with probability one in schemes of averaging and diffusion approximation.